X-ray diffraction and in vivo studies reveal the quinary structure of Trypanosoma cruzi nucleoside diphosphate kinase 1: a novel helical oligomer structure - Gómez Barroso, Juan Arturo (2022)
Trypanosoma cruzi is a flagellated protozoan parasite that causes Chagas disease, which represents a serious health problem in the Americas. Nucleoside diphosphate kinases (NDPKs) are key enzymes that are implicated in cellular energy management. TcNDPK1 is the canonical isoform in the T. cruzi parasite. TcNDPK1 has a cytosolic, perinuclear and nuclear distribution. It is also found in non-membrane-bound filaments adjacent to the nucleus. In the present work, X-ray diffraction and in vivo studies of TcNDPK1 are described. The structure reveals a novel, multi-hexameric, left-handed helical oligomer structure. The results of directed mutagenesis studies led to the conclusion that the microscopic TcNDPK1 granules observed in vivo in T. cruzi parasites are made up by the association of TcNDPK1 oligomers. In the absence of experimental data, analysis of the interactions in the X-ray structure of the TcNDPK1 oligomer suggests the probable assembly and disassembly steps: dimerization, assembly of the hexamer as a trimer of dimers, hexamer association to generate the left-handed helical oligomer structure and finally oligomer association in a parallel manner to form the microscopic TcNDPK1 filaments that are observed in vivo in T. cruzi parasites. Oligomer disassembly takes place on the binding of substrate in the active site of TcNDPK1, leading to dissociation of the hexamers. This study constitutes the first report of such a protein arrangement, which has never previously been seen for any protein or NDPK. Further studies are needed to determine its physiological role. However, it may suggest a paradigm for protein storage reflecting the complex mechanism of action of TcNDPK1.